IMPERIAL HISTORY AND BROADENING HISTORICAL CONSCIOUSNESS IN LATE MING CHINA. (May 2015) - Ditmanson, Peter
Abstract : The evolution of Ming politics was strongly shaped by the development of an expanding interest in the history of the court and the dynasty. In the early years, records of the court were tightly controlled at the capital. But, by the sixteenth century, these records could no longer be controlled and private historiography flourished, competing with and challenging the official history of the dynasty.